2014
DOI: 10.1093/nar/gku444
|View full text |Cite
|
Sign up to set email alerts
|

Engineering anAcinetobacterregulon for biosensing and high-throughput enzyme screening inE. colivia flow cytometry

Abstract: We created a single cell sorting system to screen for enzyme activity in Escherichia coli producing 3,4 dihydroxy benzoate (34DHB). To do so, we engineered a transcription factor regulon controlling the expression of green fluorescent protein (GFP) for induction by 34DHB. An autoregulated transcription factor, pcaU, was borrowed from Acinetobacter sp ADP1 to E. coli and its promoter region adapted for activity in E. Coli. The engineered pcaU regulon was inducible at >5 μM exogenous 34DHB, making it a sensitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 26 publications
3
77
0
Order By: Relevance
“…In contrast, genetically encoded biosensors have enabled FACS to be used for inconspicuous compounds. These studies have shown that biosensor-based FACS can be successful with maximum dynamic ranges as low as 12-fold, indicating that even poorly operating biosensor systems enable multiplexed phenotype evaluation (34). Implementing FACS with our techniques for real-time monitoring of whole pathway biosynthesis will enable greater versatility for phenotype evaluation in metabolic engineering.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, genetically encoded biosensors have enabled FACS to be used for inconspicuous compounds. These studies have shown that biosensor-based FACS can be successful with maximum dynamic ranges as low as 12-fold, indicating that even poorly operating biosensor systems enable multiplexed phenotype evaluation (34). Implementing FACS with our techniques for real-time monitoring of whole pathway biosynthesis will enable greater versatility for phenotype evaluation in metabolic engineering.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, Fox and coworkers showed that 34DHB could be generated in Escherichia coli , but the critical enzyme, dehydroshikimate dehydratase, is suboptimal in activity and stability. As a prelude to library‐based optimization for this enzyme we were motivated to create an in vivo , single‐cell, selectable, reporter for 34DHB that operates in same strain of E. coli . In this work, we rationally redesign a TF that has no nascent activity to 34DHB.…”
Section: Introductionmentioning
confidence: 99%
“…To further confirm the antibacterial activity of silica‐supported AgNPs against E. coli , flow cytometry was used to quantitatively measure the bacterial growth . After incubation with PI and 20 s irradiation, approximately 99% of E. coli remained viable with increased PI signal and these bacteria were consequently referred to as “live”.…”
Section: Resultsmentioning
confidence: 99%